A Comprehensive Review on Scatter Search: Techniques, Applications, and Challenges. (31st May 2021) - Kalra, Minakshi; Tyagi, Shobhit; Kumar, Vijay; Kaur, Manjit; Mashwani, Wali Khan; Shah, Habib; Shah, Kamal
Abstract : Recent years have witnessed the use of metaheuristic algorithms to solve the optimization problems that usually require extensive computations and time. Among others, scatter search is the widely used evolutionary metaheuristic algorithm. It uses the information of global optima, which is stored in a different and unique set of solutions. In this paper, an updated review of scatter search (SS) is given. SS has been successfully applied in a variety of research problems, namely, data mining, bioinformatics, and engineering design. This paper presents the modified and hybrid versions of SS with their applications. The control strategies are discussed to show their impact on the performance of SS. various issues and future directions related to SS are also discussed. It inspires innovative researchers to use this algorithm for their research domains.